Optimal minimum velocity threshold to estimate the 1-repetition maximum: the case of the smith machine bench press exercise - García-Ramos, A. (International Journal of Sports Physiology and Performance, 2023)
To compare the accuracy in the estimation of the Smith machine bench press 1-repetition maximum (1RM) when using a novel minimum velocity threshold (MVT) called optimal MVT (MVT that minimizes the differences between the actual and predicted 1RM in a preliminary session) with respect to using the 2 standard MVTs (general and individual MVTs). Methods: A total of 126 young men (Smith machine bench press 1RM = 80.7 [13.6] kg) completed 2 identical sessions consisting of an incremental loading test until reaching the 1RM load. Four individual load-velocity relationships were modeled in each session considering all loading conditions until reaching the load that showed the closest mean velocity to 0.60, 0.50, 0.40, and 0.30 m·s-1 . The first testing session was used to determine the preindividual MVT and 4 optimal MVTs (1 for each final test velocity), while the second testing session was used to estimate the 1RM using 4 types of MVT (general MVT, preindividual MVT, actual-individual MVT, and optimal MVT). Results: The absolute errors in the prediction of the 1RM were significantly lower for the optimal MVT (2.94 [2.40] kg) compared to the general MVT (3.66 [2.99] kg), preindividual MVT (3.80 [3.15] kg), and actual-individual MVT (4.02 [3.21] kg). The optimal MVT (intraclass correlation coefficient [ICC] ranged from .56 to .62) was always more reliable than the individual MVT (ICC = .34). Conclusions: The optimal MVT provides more accurate estimates of the Smith machine bench press 1RM than the standard MVTs previously used in scientific research (general and individual MVTs).